Why Ireland starved after three decades: The great famine in cross-section reconsidered - Morgan Kelly; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2015)
This short paper revisits two questions that were central to Joel Mokyr's Why Ireland Starved (2nd edition, 1985). These are, first, what determined the variation in population change across Ireland during the Great Famine decade of 1841-1851 and, second, whether and in what sense can pre-famine Ireland be characterized as 'malthusian'.
Keywords: N3; B3; 330; famine; Malthus; population; Ireland